VARIOUS APPROACHES TO TERMINOLOGY - Bakhtiyorovna, Norova Mehri; Islamovna, Vosiyeva Shahnoza (International Journal of Psychosocial Rehabilitation, 2025)
Terminology is a set of terms of a given industry of production, activity, knowledge, forming a special sector of vocabulary, most accessible to conscious regulation and streamlining. It is based not only on professional knowledge, but also on the availability of suf icient grounds for terminology or possible concepts. Terminology is a combination of scientific and technical concepts and serves for scientific, educational or industrial communication. This article provides dif erent approaches toward terminology and identifies peculiarities of it.